STRUKTUR KEPRIBADIAN MANUSIA DALAM PSIKOANALISIS SIGMUND FREUD: PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Ishom Fuadi Fikri; Syarof Nursyah Ismail; Husniyatus Salamah Zainiyati; Nur Kholis (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
This article aims to describe the structure of human personality according to Freud's psychoanalysis and how the perspective of Islamic educational philosophy regarding this concept. Descriptive-deductive approach based on the literature review was used to get all data. The results show that Freud's theory of personality underwent two stages of theoretical development; 1) the levels of human personality that were formulated before the 1920 (consciousness, pre-consciousness, unconsciousness) and 2) the structure of human personality which was formulated in 1923 (Id, Ego, Superego) to refine the previous theory. Freud's thought in line with the Islamic educational theory where human life in early childhood and its growing environment are important factors in personality formation. In Islamic education, the formation of the personality of students is centered on the internalization of good morals through purification of the soul (tazkiyah al-nafs) to achieve a personality that is in harmony with the concept of a perfect human being (insan kamil).